Contribution of Iranian Researchers in Dental Science Production as Indexed in Web of Science From 2000 to 2009 - Neda Zeraatkar; Narges Vara; Seyed Javad Ghazi Mirsaeid (Islamic Dental Association of Iran, 2012)
Background and Aim : Nowadays the most significant indicator for scientific production is the number of scientific articles that are indexed in certificated databases. Evaluation of the scientific production has become so significant as an important aspect of research and scientific production, in the way that today production and consumption of information in different communities is one of the growth and development indicators. The aim of this article is to investigate 10-years of scientific production of Iranian dentistry community in the ISI .   Materials and Methods : In this article ten years of scientific production in dentistry in ISI database was investigated using bibliometric method. Therefore, our search was limited to Iran and dentistry during 2000-2009, and the retrieved items were analyzed .   Results : It was shown that a total of 383 documents have been produced and published in this time period, among which 350 (91.4%) was authored by dental professionals in 10 Iranian universities. In this regard, Tehran University of medical sciences researchers have authored 30/8% of all productions. The most international cooperation of the Iranian dentistry researchers has been with the researchers of USA with 28 articles followed by Australia, England and Finland. Concerning journals publishing the research of the Iranian dental community, the Journal of Endodontics, has published 34 documents of all productions in this realm .   Conclusion : Our search showed that the scientific productivity of Iranian dentists has been ascending in these years. The growth reached the top in 2009, and became doubled compared with the previous year and ten times more than those in 2000 .